PERIDONTITIS AND METHODS OF THEIR TREATMENT, WHICH ARE FOUND IN MILK AND PERMANENT TEETH IN CHILDREN - Nasullayeva Shahribonu Hayot qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Anatomy: peridontitis, which occurs in milk and permanent teeth in children, is very common. For this reason, this article covers what clinical manifestations occur in the BoLS, what complications they cause, and how this can be prevented, or the effectiveness of adequate treatment. It has also been reported on which cases to get or not to get teeth.